Treating the children of the poor: institutions and the construction of medical authority in eighteenth-century London - Mathisen, A (2011)
It is commonly accepted that, prior to the rise of paediatric medicine as a formal medical specialisation in the nineteenth and twentieth centuries, medical care of children was primarily conducted by women in the context of the household. However, as this thesis argues, there was vibrant medical interest in children prior to the development of formalized paediatric medicine. Over the course of the eighteenth century, a network of medical practitioners interested in children’s health sought to establish their authority over the subject and, in doing so, devoted increased attention to children, channelling general medical interest into the basis for future medical specialisation. As this thesis argues, medical authority over children’s health was gradually constructed over the eighteenth century through printed texts, institutional experience, medical understandings of disease, and efforts to devise therapeutic practices suitable to children. Key to these developments were the efforts made by medical men to supplant women as authorities on children’s health. Also crucial was the role played by institutions in providing spaces for medical practitioners to encounter children. Institutions, such as the Dispensary for the Infant Poor and the London Foundling Hospital, increased the opportunities for medical practitioners to gain experience treating child patients. As this thesis demonstrates, it was the children of the poor who provided medical practitioners with the hands-on experience necessary to bolster their emerging claims of authority. As such, institutions and poor children both had essential roles to play in the development of medical interest in children, and the translation of that interest into claims of medical authority.